Fluorine-containing coating and application thereof

By using fluorine-containing coatings composed of alkyl phenolic resins and fluorine-carbon chain modified phenolic resins, combined with physical vapor deposition technology, the migration problem of fluorine-containing coatings when applied on non-polar substrates is solved, and the fingerprint resistance of the coating is improved Performance and service life.

CN119463619AInactive Publication Date: 2025-02-18SHENZHEN FINE NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411673297.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When fluorine-containing coatings are used on non-polar substrates, fluorine-containing compounds easily migrate to the surface of the substrate, resulting in a reduced utilization rate and affecting the adhesion firmness of the coating.

Method used

A fluorine-containing coating consisting of alkyl phenolic resin (component A) and fluorine-carbon chain modified phenolic resin (component B) is used to coat components A and component B in sequence through physical vapor deposition technology to form a coating. The non-polar groups of component A are compatible with the non-polar substrate, inhibit the migration of component B, and promote its migration to the coating surface, thereby improving utilization.

Benefits of technology

It improves the fingerprint resistance and service life of the coating, enhances the adhesion between the coating and the substrate, and avoids the reduction in the utilization rate of fluorine-containing compounds and the coating peeling problems.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a fluorine-containing coating and application thereof, the coating comprises a component A and a component B, the component A is alkyl phenolic resin, and the component B is fluorocarbon chain modified phenolic resin. According to the scheme, phenolic resin with two components is used as the coating, alkyl phenolic resin of the component A has good compatibility with a polar base material and a non-polar base material, chemical bonds or physical winding can be formed, and therefore good adhesion is achieved, the component A contains polar groups and non-polar groups, and when the coating is applied to the non-polar base material, the non-polar base material is not prone to falling off. Non-polar groups in the component A are enriched on one side of the non-polar base material due to similar compatibility, and polar groups are far away from one side of the non-polar base material, so that the component B can be inhibited from migrating to one side of the non-polar base material, the component B is promoted to migrate to the surface of the coating, the utilization rate of the component B is increased, the component B is prevented from influencing the adhesion effect of the coating, and the service life of the coating is prolonged. And the service life of the coating is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a fluorine-containing coating and application thereof. Background Art

[0002] Coatings are widely used in various fields, such as coatings for display panels. Coatings for display panels can form a high-transparency coating on the display panel. It is a key screen protection material and plays an important role in improving display quality, user experience and display life. The anti-fingerprint performance of a coating refers to the ability of the coating formed after the coating is applied to the surface of an object to effectively reduce fingerprint residues. Fingerprints contain not only oils and fats but also aqueous components such as sweat. Therefore, the coating formed by the coating needs to have hydrophobic and oleophobic properties. Fluorine-containing compounds have excellent properties such as low surface tension, low wettability and low friction. Adding fluorine-containing compounds to the coating helps to improve the anti-fingerprint performance of the coating. However, after the coating containing fluorine-containing compounds is applied as a coating, the fluorine-containing compounds in the coating will migrate from the inside to the surface. When the coating is applied to a polar substrate, the fluorine-containing compounds only migrate to the air side, which can improve the anti-fingerprint effect of the air side; when the coating is applied to a non-polar substrate, the fluorine-containing compounds can be adsorbed on the surface of the non-polar substrate, so that both the air side and the substrate side of the coating are enriched with fluorine-containing compounds. On the one hand, this leads to a decrease in the utilization rate of the fluorine-containing compounds. On the other hand, the fluorine-containing compounds enriched on the substrate surface will reduce the wetting effect of the coating and the substrate, affecting the firmness of the coating adhesion.

[0003] Therefore, it is necessary to propose a fluorine-containing coating and application thereof. Summary of the invention

[0004] In order to solve the application problem of fluorine-containing coatings on non-polar substrates, the purpose of the present invention is to provide a fluorine-containing coating and its application.

[0005] A fluorine-containing coating comprises component A and component B, wherein component A is an alkylphenol-formaldehyde resin and component B is a carbon-fluorine chain-modified phenol-formaldehyde resin.

[0006] This scheme uses two components of phenolic resin as the coating. The alkylphenolic resin of component A has good compatibility with both polar substrates and non-polar substrates, and can form chemical bonds or physical entanglements, thereby having good adhesion. Component A contains polar groups and non-polar groups. When the coating is applied to a non-polar substrate, the non-polar groups in component A are enriched on the non-polar substrate side due to similar compatibility, while the polar groups are away from the non-polar substrate side. This can inhibit component B from migrating to the non-polar substrate side and promote component B to migrate to the coating surface, thereby improving the utilization rate of component B and preventing component B from affecting the adhesion effect of the coating. At the same time, both component A and component B have hydroxyl groups, which can form hydrogen bonds, which can further improve the strength of the coating and increase the service life of the coating.

[0007] Furthermore, the carbon fluorine chain modified phenolic resin is obtained by reacting phenolic resin with a hydroxyl functional group fluorine chain extender and a fluorinated carboxylic acid. Furthermore, the hydroxyl functional group fluorine chain extender is a perfluoropolyether polyol.

[0008] Furthermore, the alkylphenol-formaldehyde resin is p-tert-butylphenol-formaldehyde resin.

[0009] The second aspect of the present invention provides an application of the above-mentioned fluorine-containing coating, comprising the following steps: applying the component A and the component B sequentially to the surface of a substrate by physical vapor deposition to form a coating, wherein the surface of the substrate is a non-polar surface.

[0010] When the above coating is applied to the surface of a non-polar substrate, the non-polar groups in component A are enriched on the non-polar substrate side due to similar compatibility, while the polar groups are far away from the non-polar substrate side, which can inhibit the migration of component B to the non-polar substrate side, thereby improving the utilization rate of component B and preventing component B from affecting the adhesion effect of the coating. At the same time, component B can form hydrogen bonds with the polar groups of component A, thereby promoting the combination of component B and component A, and improving the strength and service life of the coating.

[0011] Furthermore, the surface of the substrate comprises a silicon dioxide layer, which is obtained by evaporating silicon dioxide on a glass surface. By forming a silicon dioxide layer on the surface of the substrate, the strength of the substrate can be improved, but at the same time, the silicon dioxide layer is non-polar, and it is difficult to achieve a good adhesion effect if a conventional fluorine-containing coating is used, while the coating of this scheme can achieve a good adhesion effect on the surface.

[0012] Furthermore, the thickness of the coating is 20-40 nm. If the coating thickness is too small, it is difficult to provide a better touch effect; if the coating thickness is too large, it will affect the wear resistance and fingerprint resistance of the coating.

[0013] Further, the coating comprises a coating of component A and a coating of component B, and the thickness ratio of the coating of component A to the coating of component B is (2-3):(2-3). Further, the thickness ratio of the coating of component A to the coating of component B is 1:1.

[0014] Furthermore, the temperature of the deposition chamber during the physical vapor deposition is 50-150° C. Within this temperature range, the fluorine-containing coating has a better coating effect. DETAILED DESCRIPTION

[0015] For ease of understanding of the application, the application will be described more fully below. The application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.

[0016] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0018] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0019] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0020] The percentage contents involved in this application, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.

[0021] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.

[0022] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.

[0023] The "particles" mentioned in this application, or materials with a defined particle size distribution, are not necessarily spherical in shape, but may be irregular, primary particles or secondary particles. The particle size of irregular particles is the average of their maximum diameter and minimum diameter.

[0024] Example 1: In this example, component A of the fluorine-containing coating is tert-butyl phenolic resin (CAS No.: 25085-50-1), and component B is carbon fluorine chain modified phenolic resin. In this example, the substrate is glass, and a 10 nm silicon dioxide layer is formed on the glass surface by evaporating silicon dioxide. In this example, the sample is cut into 10 cm*10 cm specifications for standby use.

[0025] The preparation method of component B is as follows: 100g of phenolic resin (CAS No.: 9003-35-4), 2g of N,N'-diisopropylcarbodiimide (CAS No.: 693-13-0), 5g of perfluoropolyether diol (McLean P910027, CAS No.: 90317-77-4, molecular weight 5000) and 20g of perfluoropentanoic acid (CAS No.: 2706-90-3) are dissolved in dichloromethane, reacted at room temperature for 16h, and separated by a chromatographic column to obtain a carbon-fluorine chain-modified phenolic resin.

[0026] 2 g of component A was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe, and 2 g of component B was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe.

[0027] Physical vapor deposition: Place the above stainless steel container into an E-Beam 2050 (produced by United Vacuum Co., Ltd.), place the substrate sample on the top of the equipment, close the hatch, and place the sample on the top of the equipment at 3×10 -4 Argon gas was injected under a vacuum condition of 3×10 Torr to generate plasma, and the substrate sample was etched for 60 seconds. Then, when the vacuum condition reached 3×10 -5Torr and the temperature of the deposition chamber reached 50°C, the electron beam was turned on, and component A with a thickness of 12 nm and component B with a thickness of 18 nm were sequentially coated on the surface of the substrate sample to form a coating after curing, and the coating thickness was 30 nm.

[0028] Example 2: In this example, component A of the fluorine-containing coating is tert-butyl phenolic resin (CAS No.: 25085-50-1), and component B is carbon fluorine chain modified phenolic resin. In this example, the substrate is glass, and a 10 nm silicon dioxide layer is formed on the glass surface by evaporating silicon dioxide. In this example, the sample is cut into 10 cm*10 cm specifications for standby use.

[0029] The preparation method of component B is as follows: 100g of phenolic resin (CAS No.: 9003-35-4), 2g of N,N'-diisopropylcarbodiimide (CAS No.: 693-13-0), 5g of perfluoropolyether diol (McLean P910027, CAS No.: 90317-77-4, molecular weight 5000) and 20g of perfluoropentanoic acid (CAS No.: 2706-90-3) are dissolved in dichloromethane, reacted at room temperature for 16h, and separated by a chromatographic column to obtain a carbon-fluorine chain-modified phenolic resin.

[0030] 2 g of component A was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe, and 2 g of component B was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe.

[0031] Physical vapor deposition: Place the above stainless steel container into an E-Beam 2050 (produced by United Vacuum Co., Ltd.), place the substrate sample on the top of the equipment, close the hatch, and place the sample on the top of the equipment at 3×10 -4 Argon gas was injected under a vacuum condition of 3×10 Torr to generate plasma, and the substrate sample was etched for 60 seconds. Then, when the vacuum condition reached 3×10 -5 Torr and the temperature of the deposition chamber reached 50°C, the electron beam was turned on, and component A with a thickness of 18 nm and component B with a thickness of 12 nm were sequentially coated on the surface of the substrate sample to form a coating after curing, and the coating thickness was 30 nm.

[0032] Example 3: In this example, component A of the fluorine-containing coating is p-tert-butylphenol-formaldehyde resin (CAS No.: 25085-50-1), and component B is carbon fluorine chain-modified phenol-formaldehyde resin. In this example, the substrate is glass, and a 10 nm silicon dioxide layer is formed on the glass surface by evaporating silicon dioxide. In this example, the sample is cut into 10 cm*10 cm specifications for standby use.

[0033] The preparation method of component B is as follows: 100g of phenolic resin (CAS No.: 9003-35-4), 2g of N,N'-diisopropylcarbodiimide (CAS No.: 693-13-0), 5g of perfluoropolyether diol (McLean P910027, CAS No.: 90317-77-4, molecular weight 5000) and 20g of perfluoropentanoic acid (CAS No.: 2706-90-3) are dissolved in dichloromethane, reacted at room temperature for 16h, and separated by a chromatographic column to obtain a carbon-fluorine chain-modified phenolic resin.

[0034] 2 g of component A was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe, and 2 g of component B was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe.

[0035] Physical vapor deposition: Place the above stainless steel container into an E-Beam 2050 (produced by United Vacuum Co., Ltd.), place the substrate sample on the top of the equipment, close the hatch, and place the sample on the top of the equipment at 3×10 -4 Argon gas was injected under a vacuum condition of 3×10 Torr to generate plasma, and the substrate sample was etched for 60 seconds. Then, when the vacuum condition reached 3×10 -5 Torr and the temperature of the deposition chamber reached 50°C, the electron beam was turned on, and component A with a thickness of 15 nm and component B with a thickness of 15 nm were sequentially coated on the surface of the substrate sample to form a coating after curing, and the coating thickness was 30 nm.

[0036] Example 4: Component A of the fluorine-containing coating in this example is p-tert-butylphenolic resin (CAS No.: 25085-50-1), and component B is carbon fluorine chain modified phenolic resin Macklin P910027, CAS No.: 90317-77-4, molecular weight 5000. In this example, the substrate is glass, and a 10nm silicon dioxide layer is formed on the glass surface by evaporating silicon dioxide. In this example, the sample is cut into 10cm*10cm specifications for standby use.

[0037] The preparation method of component B is as follows: 100g of phenolic resin (CAS No.: 9003-35-4), 2g of N,N'-diisopropylcarbodiimide (CAS No.: 693-13-0), 20g of perfluoropolyether diol (McLean P910027, CAS No.: 90317-77-4, molecular weight 5000) and 20g of perfluoropentanoic acid (CAS No.: 2706-90-3) are dissolved in dichloromethane, reacted at room temperature for 16h, and separated by a chromatographic column to obtain a carbon-fluorine chain-modified phenolic resin.

[0038] 2 g of component A was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe, and 2 g of component B was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe.

[0039] Physical vapor deposition: Place the above stainless steel container into an E-Beam 2050 (produced by United Vacuum Co., Ltd.), place the substrate sample on the top of the equipment, close the hatch, and place the sample on the top of the equipment at 3×10 -4 Argon gas was injected under a vacuum condition of 3×10 Torr to generate plasma, and the substrate sample was etched for 60 seconds. Then, when the vacuum condition reached 3×10 -5 Torr and the temperature of the deposition chamber reached 50°C, the electron beam was turned on, and component A with a thickness of 12 nm and component B with a thickness of 18 nm were sequentially coated on the surface of the substrate sample to form a coating after curing, and the coating thickness was 30 nm.

[0040] Example 5: Component A of the fluorine-containing coating in this example is tert-butyl phenolic resin (CAS No.: 25085-50-1), and component B is carbon fluorine chain modified phenolic resin Macklin P910027, CAS No.: 90317-77-4, molecular weight 5000. In this example, the substrate is polytetrafluoroethylene, and the sample is cut into 10cm*10cm size for standby use.

[0041] The preparation method of component B is as follows: 100g of phenolic resin (CAS No.: 9003-35-4), 2g of N,N'-diisopropylcarbodiimide (CAS No.: 693-13-0), 5g of perfluoropolyether diol (McLean P910027, CAS No.: 90317-77-4, molecular weight 5000) and 20g of perfluoropentanoic acid (CAS No.: 2706-90-3) are dissolved in dichloromethane, reacted at room temperature for 16h, and separated by a chromatographic column to obtain a carbon-fluorine chain-modified phenolic resin.

[0042] 2 g of component A was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe, and 2 g of component B was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe.

[0043] Physical vapor deposition: Place the above stainless steel container into an E-Beam 2050 (produced by United Vacuum Co., Ltd.), place the substrate sample on the top of the equipment, close the hatch, and place the sample on the top of the equipment at 3×10 -4 Argon gas was injected under a vacuum condition of 3×10 Torr to generate plasma, and the substrate sample was etched for 60 seconds. Then, when the vacuum condition reached 3×10 -5 Torr and the temperature of the deposition chamber reached 50°C, the electron beam was turned on, and component A with a thickness of 12 nm and component B with a thickness of 18 nm were sequentially coated on the surface of the substrate sample to form a coating after curing, and the coating thickness was 30 nm.

[0044] Example 6: Component A of the fluorine-containing coating in this example is p-tert-butylphenolic resin (CAS No.: 25085-50-1), and component B is carbon fluorine chain modified phenolic resin Macklin P910027, CAS No.: 90317-77-4, molecular weight 5000. In this example, the substrate is glass, and a 10nm silicon dioxide layer is formed on the glass surface by evaporating silicon dioxide. In this example, the sample is cut into 10cm*10cm specifications for standby use.

[0045] The preparation method of component B is as follows: 100g of phenolic resin (CAS No.: 9003-35-4), 2g of N,N'-diisopropylcarbodiimide (CAS No.: 693-13-0), 5g of perfluoropolyether diol (McLean P910027, CAS No.: 90317-77-4, molecular weight 5000) and 20g of perfluoropentanoic acid (CAS No.: 2706-90-3) are dissolved in dichloromethane, reacted at room temperature for 16h, and separated by a chromatographic column to obtain a carbon-fluorine chain-modified phenolic resin.

[0046] 2 g of component A was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe, and 2 g of component B was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe.

[0047] Physical vapor deposition: Place the above stainless steel container into an E-Beam 2050 (produced by United Vacuum Co., Ltd.), place the substrate sample on the top of the equipment, close the hatch, and place the sample on the top of the equipment at 3×10 -4 Argon gas was injected under a vacuum condition of 3×10 Torr to generate plasma, and the substrate sample was etched for 60 seconds. Then, when the vacuum condition reached 3×10 -5 Torr and the temperature of the deposition chamber reached 50°C, the electron beam was turned on, and component A with a thickness of 16 nm and component B with a thickness of 24 nm were sequentially coated on the surface of the substrate sample to form a coating after curing, and the coating thickness was 40 nm.

[0048] Example 7: Example 1: In this example, component A of the fluorine-containing coating is tert-butyl phenolic resin (CAS No.: 25085-50-1), and component B is carbon fluorine chain modified phenolic resin Macklin P910027, CAS No.: 90317-77-4, molecular weight 5000. In this example, the substrate is glass, and a 10nm silicon dioxide layer is formed on the glass surface by evaporating silicon dioxide. In this example, the sample is cut into 10cm*10cm specifications for standby use.

[0049] The preparation method of component B is as follows: 100g of phenolic resin (CAS No.: 9003-35-4), 2g of N,N'-diisopropylcarbodiimide (CAS No.: 693-13-0), 5g of perfluoropolyether diol (McLean P910027, CAS No.: 90317-77-4, molecular weight 5000) and 20g of perfluoropentanoic acid (CAS No.: 2706-90-3) are dissolved in dichloromethane, reacted at room temperature for 16h, and separated by a chromatographic column to obtain a carbon-fluorine chain-modified phenolic resin.

[0050] 2 g of component A was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe, and 2 g of component B was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe.

[0051] Physical vapor deposition: Place the above stainless steel container into an E-Beam 2050 (produced by United Vacuum Co., Ltd.), place the substrate sample on the top of the equipment, close the hatch, and place the sample on the top of the equipment at 3×10 -4 Argon gas was injected under a vacuum condition of 3×10 Torr to generate plasma, and the substrate sample was etched for 60 seconds. Then, when the vacuum condition reached 3×10 -5 Torr and the temperature of the deposition chamber reached 150°C, the electron beam was turned on, and component A with a thickness of 8 nm and component B with a thickness of 12 nm were sequentially coated on the surface of the substrate sample to form a coating after curing, and the coating thickness was 20 nm.

[0052] Example 8: Component A of the fluorine-containing coating in this example is p-tert-butylphenolic resin (CAS No.: 25085-50-1), and component B is carbon fluorine chain modified phenolic resin Macklin P910027, CAS No.: 90317-77-4, molecular weight 5000. In this example, the substrate is glass, and a 10nm silicon dioxide layer is formed on the glass surface by evaporating silicon dioxide. In this example, the sample is cut into 10cm*10cm specifications for standby use.

[0053] The preparation method of component B is as follows: 100g of phenolic resin (CAS No.: 9003-35-4), 2g of N,N'-diisopropylcarbodiimide (CAS No.: 693-13-0), 5g of perfluoropolyether diol (McLean P910026, CAS No.: 90317-77-4, molecular weight 1000) and 20g of perfluoropentanoic acid (CAS No.: 2706-90-3) are dissolved in dichloromethane, reacted at room temperature for 16h, and separated by a chromatographic column to obtain a carbon-fluorine chain-modified phenolic resin.

[0054] 2 g of component A was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe, and 2 g of component B was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe.

[0055] Physical vapor deposition: Place the above stainless steel container into an E-Beam 2050 (produced by United Vacuum Co., Ltd.), place the substrate sample on the top of the equipment, close the hatch, and place the sample on the top of the equipment at 3×10 -4 Argon gas was injected under a vacuum condition of 3×10 Torr to generate plasma, and the substrate sample was etched for 60 seconds. Then, when the vacuum condition reached 3×10 -5 Torr and the temperature of the deposition chamber reached 50°C, the electron beam was turned on, and component A with a thickness of 12 nm and component B with a thickness of 18 nm were sequentially coated on the surface of the substrate sample to form a coating after curing, and the coating thickness was 30 nm.

[0056] Comparative Example 1: The fluorine-containing coating in this comparative example only contains component B, which is a carbon fluorine chain-modified phenolic resin. In this comparative example, the substrate is glass, and a 10 nm silicon dioxide layer is formed on the glass surface by evaporating silicon dioxide. In this comparative example, samples of 10 cm*10 cm in size are cut for later use.

[0057] The preparation method of component B is as follows: 100g of phenolic resin (CAS No.: 9003-35-4), 2g of N,N'-diisopropylcarbodiimide (CAS No.: 693-13-0), 5g of perfluoropolyether diol (McLean P910027, CAS No.: 90317-77-4, molecular weight 5000) and 20g of perfluoropentanoic acid (CAS No.: 2706-90-3) are dissolved in dichloromethane, reacted at room temperature for 16h, and separated by a chromatographic column to obtain a carbon-fluorine chain-modified phenolic resin.

[0058] 2 g of component B was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe.

[0059] Physical vapor deposition: Place the above stainless steel container into an E-Beam 2050 (produced by United Vacuum Co., Ltd.), place the substrate sample on the top of the equipment, close the hatch, and place the sample on the top of the equipment at 3×10 -4 Argon gas was injected under a vacuum condition of 3×10 Torr to generate plasma, and the substrate sample was etched for 60 seconds. Then, when the vacuum condition reached 3×10 -5 Torr and the temperature of the deposition chamber reached 50°C, the electron beam was turned on, and component B with a thickness of 30 nm was coated on the surface of the substrate sample. After curing, a coating with a thickness of 30 nm was formed.

[0060] Comparative Example 2: Component A of the fluorine-containing coating in this comparative example is p-tert-butylphenol-formaldehyde resin (CAS No.: 25085-50-1), and component B is carbon fluorine chain-modified phenol-formaldehyde resin. In this comparative example, the substrate is glass, and a 10 nm silicon dioxide layer is formed on the glass surface by evaporating silicon dioxide. In this comparative example, samples of 10 cm*10 cm in size are cut for standby use.

[0061] The preparation method of component B is as follows: 100g of phenolic resin (CAS No.: 9003-35-4), 2g of N,N'-diisopropylcarbodiimide (CAS No.: 693-13-0), 5g of perfluoropolyether diol (McLean P910027, CAS No.: 90317-77-4, molecular weight 5000) and 20g of perfluoropentanoic acid (CAS No.: 2706-90-3) are dissolved in dichloromethane, reacted at room temperature for 16h, and separated by a chromatographic column to obtain a carbon-fluorine chain-modified phenolic resin.

[0062] 2 g of component A was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe, and 2 g of component B was injected into a stainless steel container with a diameter of 2 cm and filled with carbon felt using a syringe.

[0063] Physical vapor deposition: Place the above stainless steel container into an E-Beam 2050 (produced by United Vacuum Co., Ltd.), place the substrate sample on the top of the equipment, close the hatch, and place the sample on the top of the equipment at 3×10 -4 Argon gas was injected under a vacuum condition of 3×10 Torr to generate plasma, and the substrate sample was etched for 60 seconds. Then, when the vacuum condition reached 3×10 -5 Torr and the temperature of the deposition chamber reached 50°C, the electron beam was turned on, and component A with a thickness of 3 nm and component B with a thickness of 27 nm were sequentially coated on the surface of the substrate sample to form a coating after curing, and the coating thickness was 30 nm.

[0064] The coatings of the above embodiments and comparative examples were subjected to performance tests.

[0065] Contact angle test: The contact angle of the coating surface to water was tested by a contact angle meter. The results are shown in Table 1.

[0066] The test method of the wear resistance test is as follows: using an eraser tester (purchased from CORETECH CORP), the above sample is fixed on a fixed plate, a cylindrical eraser with a diameter of 5 mm is installed, a weight load of 1 kg is applied to the substrate, the round-trip length is 40 mm, the round-trip speed is 40 r / min, and the water drop contact angle on the substrate surface at 20,000, 3,000 and 20,000 round-trips is taken as the average of 5 measurements. The test data is shown in Table 1.

[0067] Table 1 Test results project Initial contact angle 3000 times contact angle 20000 contact angle Example 1 116.3 114.1 110.7 Example 2 118.5 113.8 109.2 Example 3 118.7 115.2 112.4 Example 4 115.9 114.0 110.3 Example 5 116.5 114.4 111.2 Example 6 116.8 114.6 111.3 Example 7 116.4 113.2 108.9 Example 8 116.6 114.4 111.0 Comparative Example 1 119.1 Shedding Shedding Comparative Example 2 118.4 102.2 Shedding According to the data in Table 1, both the embodiments and the comparative examples have a better initial contact angle. This is because component B contains a fluorocarbon chain, which can provide good hydrophobic and oleophobic effects for the coating and thus has a larger contact angle. However, the coating in comparative example 1 quickly fell off during the wear resistance test. This is because the wetting effect of component B on the substrate is poor, which causes the coating to fall off easily. Embodiment 1-8 has better wear resistance, this is because it uses two kinds of phenolic resin as coating, the alkylphenolic resin of component A has better compatibility with polar substrate and non-polar substrate, can form chemical bond or physical entanglement, thus has better adhesion, component A contains polar group and non-polar group, when coating is applied to non-polar substrate, the non-polar group in component A is enriched on one side of non-polar substrate because of similar compatibility principle, and polar group is far away from one side of non-polar substrate, so component B can be suppressed to migrate to one side of non-polar substrate, and promote component B to migrate to coating surface, improve the utilization rate of component B, and prevent component B from affecting the adhesion effect of coating, component A and component B have hydroxyl groups at the same time, can form hydrogen bond connection, can further improve the strength of coating, improve the service life of coating. Comparative Example 2 uses thinner component A coating, after coating forms coating, it is difficult to prevent component B from migrating to one side of non-polar surface, so coating is easy to fall off during long-term use.

[0068] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0069] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A fluorine-containing coating, characterized in that: The invention comprises component A and component B, wherein component A is an alkylphenol-formaldehyde resin, and component B is a fluorocarbon chain-modified phenol-formaldehyde resin.

2. The fluorine-containing coating according to claim 1, characterized in that: The carbon fluorine chain modified phenolic resin is obtained by reacting phenolic resin with a hydroxyl functional group fluorine chain extender and a fluorinated carboxylic acid.

3. The fluorine-containing coating according to claim 2, characterized in that: The hydroxyl functional group fluorine-based chain extender is perfluoropolyether polyol.

4. The fluorine-containing coating according to claim 1, characterized in that: The alkylphenol-formaldehyde resin is p-tert-butylphenol-formaldehyde resin.

5. The use of the fluorine-containing coating according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: coating the component A and the component B on the surface of a substrate by physical vapor deposition to form a coating, wherein the surface of the substrate is a non-polar surface.

6. The use according to claim 5, characterized in that: The surface of the substrate comprises a silicon dioxide layer, which is obtained by evaporating silicon dioxide on a glass surface.

7. The use according to claim 5, characterized in that: The thickness of the coating is 20-40 nm.

8. The use according to claim 5, characterized in that: The coating comprises a coating of component A and a coating of component B, and a thickness ratio of the coating of component A to the coating of component B is (2-3):(2-3).

9. The use according to claim 8, characterized in that: The thickness ratio of the coating layer of component A to the coating layer of component B is 1:

1.

10. The use according to claim 5, characterized in that: The temperature of the deposition chamber during the physical vapor deposition is 50-150°C.